2011
DOI: 10.3945/ajcn.110.004242
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cranberry juice consumption on vascular function in patients with coronary artery disease

Abstract: Chronic cranberry juice consumption reduced carotid femoral pulse wave velocity-a clinically relevant measure of arterial stiffness. The uncontrolled pilot study suggested an acute benefit; however, no chronic effect on measures of endothelial vasodilator function was found. This trial was registered at clinicaltrials.gov as NCT00553904.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
236
1
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(262 citation statements)
references
References 40 publications
18
236
1
7
Order By: Relevance
“…The significant increase in acute FMD following consumption of the polyphenol-rich drink is consistent with other studies conducted in non-athlete populations [16][17][18][19]. For instance, FMD was increased after consumption of 477 mg of polyphenols from non-alcoholized red wine in healthy subjects [18].…”
Section: Study 1-polyphenols and Fmdsupporting
confidence: 79%
“…The significant increase in acute FMD following consumption of the polyphenol-rich drink is consistent with other studies conducted in non-athlete populations [16][17][18][19]. For instance, FMD was increased after consumption of 477 mg of polyphenols from non-alcoholized red wine in healthy subjects [18].…”
Section: Study 1-polyphenols and Fmdsupporting
confidence: 79%
“…However, among patients with the correct RHI, the consumption of olive oil did not contribute to any improvement of this parameter . Another study showed that in patients with the coronary arterial disease the endothelial function improved in 2 h after drinking the cranberry juice (480 ml) but this effect was not found in long-term research (4 weeks) (Dohadwala et al 2011).…”
Section: Resultsmentioning
confidence: 99%
“…However, we did not find that CEB consumption for 8 week improved fasting glycemic parameters in healthy overweight adults. Similarly, cranberry juice consumption for 4 week did not affect fasting glucose, insulin, or HOMA-IR in subjects with CAD [19]. Thus, the long-term benefit of cranberry polyphenols on fasting glycemic control may be more evident in people with impaired glucose control.…”
Section: Glucoregulationmentioning
confidence: 92%
“…To date, studies have explored the effect of cranberry juice on CVD risk factors in healthy subjects [10][11][12][13][14][15] as well as in patients with type 2 diabetes (T2DM) [16][17][18], coronary artery disease (CAD) [19], endothelial dysfunction [20], and metabolic syndrome [21]. However, only 2 of these trials have examined people with CVD risk factors other than hypercholesterolemia and T2DM, e.g.…”
Section: Introductionmentioning
confidence: 99%